CITRA TOKOH WANITA DALAM NOVEL AKU BUKAN BUDAK KARYA ASTINA TRIUTAMI - Riyan Susilo Putri; Abdurahman Abdurahman; Bakhtaruddin Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
The purpose of this article to describe the image of women in novel Aku Bukan Budak by Astina Triutami, the review of the two aspects , namely (a) the image of women as individuals and, (b) the image of women as members of society. The data of this study are sentences or section of novel text about the image of women. Analyzing techniques (1) described the structure of the novel Aku Bukan Budak by Astina Triutami, (2) classify data relating to the images of women, (3) interpret the data relating to the images of women, (4) analyze and inventory of data relating to the images of women, (5) concluded the research of data, (6) writing the report. The study’s findings that the image of women in novel Aku Bukan Budak by Astina Ttiutami is the image of women as an individuals involves the images of women patient, graceful, kindly and as members of the society that includes concern for others, and relationship with environment and other people.